Behavioral Economics Framework for Pension Program Participation Among Female Workers in Labor-Intensive Industries - Mercy Reyne Marlina Tirayoh; Robin; Sony Putra; Etty Sri Wahyuni (Academic Bright Collaboration, 2026)
Purpose – This study develops and empirically validates a behavioral economics framework linking framing effect and mental accounting, through financial decisions, to perceived pension program effectiveness among female workers in Batam’s labor-intensive industries. It addresses the gender pension participation gap and the retirement vulnerability of women manufacturing workers, whose pension-related decisions remain insufficiently explained by conventional financial-literacy approaches.Methods – A sequential explanatory mixed-method design was used. Quantitative data were collected from 400 female workers through cluster sampling and analyzed using SPSS and Partial Least Squares Structural Equation Modeling (PLS-SEM). The quantitative phase was complemented by in-depth interviews with 40 purposively selected respondents, with interview data thematically analyzed to contextualize the structural findings.Findings – Framing effect and mental accounting significantly and positively influence financial decisions and perceived pension program effectiveness. Financial decisions also strongly predict perceived pension program effectiveness and partially mediate the effects of framing effect and mental accounting on the outcome construct. Qualitative findings show that many workers perceive pension contributions as “money that disappears,” lack a dedicated retirement mental account, and respond positively to future-self reframing and default-enrollment mechanisms.Research implications – The findings are limited by the single-city sample, cross-sectional design, and reliance on self-reported perceptual measures rather than verified enrollment behavior. Proposed policy directions require experimental validation through randomized field trials.Originality – This study provides an empirically validated, gender-responsive behavioral economics framework for pension policy design among female workers in Indonesian labor-intensive industries.